Idiopathic intracranial hypertension. - Wakerley, B; Tan, M; Ting, E (2014)
BACKGROUND: Idiopathic intracranial hypertension or pseudotumour cerebri is primarily a disorder of young obese women characterised by symptoms and signs associated with raised intracranial pressure in the absence of a space-occupying lesion or other identifiable cause. SUMMARY: The overall incidence of idiopathic intracranial hypertension is approximately two per 100,000, but is considerably higher among obese individuals and, given the global obesity epidemic, is likely to rise further. The pathophysiology of this condition is poorly understood, but most theories focus on the presence of intracranial venous hypertension and/or increased cerebrospinal fluid outflow resistance and how this relates to obesity. A lack of randomised clinical trials has resulted in unsatisfactory treatment guidelines and although weight loss is important, especially when used in conjunction with drugs that reduce cerebrospinal fluid production, resistant cases remain difficult to manage and patients invariably undergo neurosurgical shunting procedures. The use of transverse cerebral sinus stenting remains contentious and long-term benefits are yet to be determined. CONCLUSION: An understanding of the clinical features, diagnostic work-up and therapeutic options available for patients with idiopathic intracranial hypertension is important both for neurologists and ophthalmologists as visual loss maybe permanent if untreated.